1943
DOI: 10.1152/ajplegacy.1943.138.3.512
|View full text |Cite
|
Sign up to set email alerts
|

The Rôle of Oxygen in the Metabolism and Motility of Human Spermatozoa

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
168
1
7

Year Published

1949
1949
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 334 publications
(177 citation statements)
references
References 0 publications
1
168
1
7
Order By: Relevance
“…Reactive oxygen species (ROS) are toxic to both spermatozoa and oocytes, with the former being more sensitive to high ROS concentrations (3)(4)(5)(6)(7)(8)(9)(10). MacLeod demonstrated that oxidative stress was responsible for decreases in sperm motility and that the adverse effects of increased oxygen concentrations could be mitigated by adding catalase to cultures (5).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Reactive oxygen species (ROS) are toxic to both spermatozoa and oocytes, with the former being more sensitive to high ROS concentrations (3)(4)(5)(6)(7)(8)(9)(10). MacLeod demonstrated that oxidative stress was responsible for decreases in sperm motility and that the adverse effects of increased oxygen concentrations could be mitigated by adding catalase to cultures (5).…”
mentioning
confidence: 99%
“…MacLeod demonstrated that oxidative stress was responsible for decreases in sperm motility and that the adverse effects of increased oxygen concentrations could be mitigated by adding catalase to cultures (5).…”
mentioning
confidence: 99%
See 3 more Smart Citations